2017
DOI: 10.1002/jso.24741
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of short and long term outcomes in patients undergoing immediate breast reconstruction following neoadjuvant chemotherapy

Abstract: Following NAC, risk factors for complications in patients undergoing SSM/NSM with IR are high BMI, smoking, and adjuvant XRT. SSM/NSM following NAC is associated with excellent local control. These data support expanding the indications for NSM/SSM to include patients receiving NAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…To analyze control variables, the relationships between NACT, surgery, and physical condition were compared using multivariate variance analysis, and continuous variables were evaluated using the T test. According to the literature [ 13 , 14 ], we analyzed known confounding factors, including age, BMI, smoking history, menopausal status, etc. In addition, stage and grade were investigated based on clinical experience, and this analysis allows for a more accurate comparison.…”
Section: Methodsmentioning
confidence: 99%
“…To analyze control variables, the relationships between NACT, surgery, and physical condition were compared using multivariate variance analysis, and continuous variables were evaluated using the T test. According to the literature [ 13 , 14 ], we analyzed known confounding factors, including age, BMI, smoking history, menopausal status, etc. In addition, stage and grade were investigated based on clinical experience, and this analysis allows for a more accurate comparison.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, assessment of nipple margin during surgery is mandatory (17). Several studies have reported on the feasibility of this approach in patients who receive NACT, and the LRR rates ranged between 3.2% and 10.3% (18)(19)(20)(21)(22). However, the majority of the studies involved a relatively small sample size and short follow-up durations.…”
Section: Discussionmentioning
confidence: 99%
“…We also identified a significantly higher rate of reconstruction failure at 5 years with TE/I, compared to AR, for patients with overweight BMI (25.1‐30) and obese BMI (>30), but not for patients with normal BMI (≤25). It is well established in the literature that patients with current or previous smoking history and BMI ≥ 30 have a significant higher risk of failure of reconstruction . Additionally, these factors also increase the risk of infection and data have demonstrated that the most common etiology of implant‐based reconstruction failure is infection .…”
Section: Discussionmentioning
confidence: 99%
“…It is well established in the literature that patients with current or previous smoking history and BMI ≥ 30 have a significant higher risk of failure of reconstruction. [16][17][18][19] Additionally, these factors also increase the risk of infection and data have demonstrated that the most common etiology of implant-based reconstruction failure is infection. 20 We have identified that infections account for a substantial proportion of reconstruction failures in our series.…”
Section: Discussionmentioning
confidence: 99%